THE PRAKTIKALITAS PENGEMBANGAN E-BOOK FISIKA BERBANTUAN EDMODO BERBASIS DISCOVERY LEARNING DALAM PROSES PEMBELAJARAN FISIKA - Fitrah Ayu; Ahmad Fuzi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2020)
The purpose of this research and development was to determine the level of practicality in using e-book of Physics assisted by edmodo based on discovery learning in the learning process. This type of research and Development (R&D). The method used in this research is descriptive method with data collection instruments, namely practicality questionnaires assessed by the teacher. This research was conducted at State Senior High School 14 Padang for the 2019/2020 academic year on mechanical wave material. The results of this study indicate that the e-book Physics assisted by edmodo based on discovery learning is very pratical to use in the learning process with an average percentage of practicality 90%.